The study of records management competencies by applying Kappa Coefficient in coding process for inter-coder reliability / Asmadi Mohammad Ghazali, Rusnah Johare, Mohamad Noorman Masrek - Mohammad Ghazali, Asmadi; Johare, Rusnah; Masrek, Mohamad Noorman (2011)
This study was started with the aim of exploring records management competencies for records managers in Malaysian federal ministries. The data collection methods consist of unstructured interviews, content analyses and on-line focus groups discussions. In order to identify themes and pattern of qualitative data from these methods, transcription and categorization process has been addressed by executing manifest and latent coding. The study has used NVivo8 for coding process and the input of inter-coder responses has been converted into specific tables in Microsoft Excel. 852 statements have been examined by two inter-coders by evaluating the degree of reliability and consistency of coding process by using Kappa Coefficient.